Towards nuclear geography: Zones, bodies, and communities. Issue 9 (September 2017) - Alexis‐Martin, Becky; Davies, Thom
Abstract: Since the discovery of radioactivity in 1895, ionising radiation has become an increasingly prominent part of modern life. Here, we explore the diverse modes of interaction that occur between bodies and nuclear technology and point towards the scope for further research on nuclear geographies. We bring together different strands of this nascent discipline and, by doing so, highlight how nuclear technology interacts across a spectrum of geographic scales, communities, and bodies. Although nuclear geographies can be sensational and exceptionalising, such as the experiences of nuclear accident survivors and the creation of "exclusion zones, " they can also be mundane, everyday and largely unrecognised, such as the production of nuclear energy and the life‐giving nature of radioactive medicine. To frame our discussion, we take three cuts at nuclear geography, highlighting the importance of zones, bodies, and communities. By discussing this gamut of spaces and societies created through ionising radiation, we open the way for more research into the cross section of benefits, challenges, and social phenomena that arise, as we coexist with nuclear technology.